Bubble population balance modelling for stationary and rotating columns under zero-gravity environment: Numerical study. (October 2019) - Alhendal, Yousuf; Turan, Ali; Kalendar, Abdulrahim; Abou-Ziyan, Hosny
Two axisymmetric dimensional Eulerian/Eulerian simulation of two-phase (gas/liquid) transient flow was performed for both stationary and rotating columns under zero gravity. Multiphase flow simulation is modelled using flow algorithm based on the finite-volume method to simulate bubble population balance modelling. Two coalescence kernels, one for laminar flow and the other for laminar shear flow, are experimented under zero gravity using special user defined functions. Effects of rotation speed are investigated at angular velocities of 0, 0.25, 0.5, 0.75 and 1 rad/s, and effects of air inlet velocity are conducted at 1, 2, 3 and 4 cm/s. The numerical results show that the centrifugal force is pulling the bubbles towards the axis of rotation and shifts them away from the wall. Also, rotation could accelerate the moving bubbles throughout the column under zero-gravity conditions. Increasing the inlet air velocity accelerates the coalescence rate with a decrease in the inlet bubble diameter. Under zero gravity, the bubbles are formed with limited size distribution and may not be represented by an equivalent phase with Sauter mean diameter. Coalescence and break-up phenomena must be considered under normal gravity and coalescence phenomenon only under zero gravity.